Analysis Of Collective Intelligence in The Education of University Students - Mario, Rodríguez; Alejandro, Vera; Roberto, Díaz; Juan, Reinoso; Pulido, Olga (Journal of Ecohumanism, 2024)
The objective of this research is to recognize how teamwork, collaboration, and communication can enhance students’ learning and skill acquisition. An extensive search will be conducted on collective intelligence, its tools, and how it supports collaborative learning in higher education. Surveys and interviews will be conducted with university students to gather information about their experiences and perceptions regarding teamwork and collaboration. The data analysis will determine the importance of collective intelligence in the education of university students. It will also identify the tools that allow us to develop collective intelligence to foster collaboration and teamwork, as well as to identify and design strategies to improve implementation methods in higher education and student development. The results of this research could be used to develop specific training programs for university students and to provide resources and tools that support the development of collective intelligence. Furthermore, collaboration networks could be created among students, teachers, and other members of the university community to promote knowledge exchange and innovation, there by improving academic training for their professional and personal development.